Serum Sex Hormone Binding Globulin Concentration as a Predictor of Ovarian Response During Controlled Ovarian Hyperstimulation - Zhai, Junyu; Li, Shang; Zhu, Yinci; Sun, Yun; Chen, Zi-Jiang; Du, Yanzhi (Frontiers in Medicine, 2021)
Purpose: Serum concentrations of sex hormone binding globulin (SHBG), a glycated homodimeric plasma transport protein, correlate positively with the total number of follicles in women with infertility. However, the relationship between serum SHBG concentrations and the ovarian response during controlled ovarian hyperstimulation (COH) and whether this relationship differs between women with and without polycystic ovary syndrome (PCOS) remains unclear. Methods: The study cohort included 120 participants (60 non-PCOS and 60 PCOS) undergoing in vitro fertilization. Serum samples were collected from each participant every 2–3 days during the COH cycle. The concentrations of serum SHBG and other sex hormones were determined to investigate the relationship between serum SHBG concentrations and the ovarian response in women with and without PCOS. Results: We found that the serum SHBG concentration was positively correlated with the ovarian response in non-PCOS patients but not in PCOS patients. Conclusion: The serum SHBG concentration may be clinically useful as a predictor of the ovarian response during COH in patients without PCOS.